(3GdMeGjI GdLRGFjI ddYedGJ GdJLGQjI (B:s (3OQGSI JMdjdjI ebGQfI habG dGMOK GdJTQjYGJ GdYQHjI hGdGLfHjI (B/s - (3GdSdGeGJ, fGUQ YHO GdMdjes ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2008)
(3jJfGhd GdcJGH aj eMJhGg eGjdj ebOeI ,eGgjI GdYdGeI GdJLGQjI , ehVY GdYdGeI GdJLGQjI ef GdMeGjI GdbGfhfjI , JMOjO GdYdGeI GdJLGQjI aj eMd GdMeGjI GdbGfhfjI , OhQ GdJTQjY GdYbGHj aj MeGjI GdYdGeI GdJLGQjI , YfGUQ GdfehPL GdbGfhfj dLQjeI GdJYOj Ydi GdYdGeI GdJLGQjI feGPL GdLQGFe GdhGbYI Ydi GdYdGeI GdJLGQjI , VhGHW GdeSDhdjI GdLRGFjI aj LQGFe GdJYOj Ydi GdYdGeI GdJLGQjI GdbhGYO GdGLQGFjI GdNGUI HGdOYhI GdfGTFI Yf LQGFe GdJYOj Ydi GdYdGeI GdJLGQjI (B.s
Keywords: (3JTQjYGJ GLfHjIs; (3JTQjYGJ YQHjIs; (3MeGjI LRGFjIs; (3YdGeGJ JLGQjIs